Hedysarum persicum (Hedysareae, Leguminosae), a new species from Talesh Mountains, Iran - Bidarlord, Mahmoud; Ggahremaninejad, Farrokh; Mozafarian, Valiolla (Phytotaxa, 2015)
Hedysarum persicum (Hedysareae, Leguminosae) is described and illustrated as a new species from Talesh Mountains in northwestern Iran. Diagnostic morphological characters useful in discriminating the new species from its close relative H. cappadocicum are explained. Some notes are also presented on the ecology, distribution, and conservation status of the new species.